Territorially-differentiated Elements in Lesia Ukrainka’s Artistic Language as an Object of Scientific Research (Linguostylistic Studies, 2014)
Lesia Ukrainka was the first author who used the elements of the western Polissian dialects in the emotive prose. The scholars emphasize great artistic skill with which the colloquial speech elements are conveyed in her works. The article traces the history and the main tendencies of the linguistic studies of the folk basis of Lesia Ukrainka’s artistic language. It is claimed that special studies in this field were initiated by V. F. Pokalchuk in the late 1950-ies.The researchers had become increasingly interested in this phenomenon in 1990–2000 when the methodological approaches to the research changed and strongly improved. The emphasis has been laid on the scholars’ conclusions as to the importance of usage of the territorially-differentiated lexical units in Lesia Ukrainka’s texts, especially in the stories describing Volyn and her famous poem «Forest Song». It has been stressed that most researchers of Lesia Ukrainka’s language classify these concrete language phenomena as dialectical words by comparing them with the literary standards of modern Ukrainian. The author states that it is worth to consider the phenomenon verifying it against the norms of the Naddniprianskii variant of the literary language of that time. Key words: colloquial (dialectical) language; western Polissian dialect; folk speaking language; dialectism; stylistic functions of the dialectisms. References